First colombian consensus on digestive endoscopy "agreement on fundamentals" (First part: Formative aspects) (2012)
Purpose of the work. The practice of endoscopy in Colombia was modified when Resolution 1043 of 2006 authorized specialists in general surgery, internal medicine and pediatrics to perform endoscopy after completing one year of training in endoscopy at an institution of higher education. This, together with the development of relationships with different specialties within endoscopy, generated a disordered scenario which many considered to be unjust and unequal. Training requirements became differentiated. A world of tensions and interests among specialists, scientists, health care providers and service providers led to this consensus. Starting with fundamental agreements, it makes recommendations for unification of educational features that will allow endoscopic practices which aim for quality and whose central axis is the best interest of our patients. Materials and Methods. This consensus is a descriptive, cross-sectional social research study with a mixed approach (qualitative and quantitative) based on the Delphy method. The information in this study was obtained from the event titled "Acuerdo en lo fundamental" (agreement on fundamental issues) organized on June 23, 2012 by the president of the Colombian Association of Digestive Endoscopy (ACED). Qualitative data were taken from four roundtables discussions in which 34 participants discussed 25 survey questions. The quantitative data were taken from final voting and from an individual, private electronic survey. 75% or greater agreement was defined as consensus. Qualitative analysis employed discourse analysis oriented around five variables related to formative aspects. Basic descriptive statistics centered around percentages were used for quantitative analysis. Results. Participants in the consensus included 34 directors or representatives of 8 of the 9 graduate university programs with specialties in the digestive tract, former presidents of 11 scientific associations, professors of gastrointestinal endoscopy, the vice president of the Ibero-American Nurses Association, directors of institutes of endoscopy, teachers at institutes of endoscopy and four chiefs of graduate resident programs. Some issues upon which consensus was reached include: 81.9% agreed that endoscopy is not simply a diagnostic technique; 88.2% disagreed with one year training as recommended for gastrointestinal endoscopy with quality parameters; 100% underlined that training in endoscopy should take place within qualified and accredited university teaching; More than 84.9% did not recommend training general practitioners, nurses or medical technicians in endoscopy; 85.3% recommended 2-year programs for basic training in endoscopy with 1 to 2 years for advanced endoscopy. Conclusions. The Colombian consensus agrees that endoscopy is an element of support for both diagnostic and therapeutic practice. Training for quality endoscopy requires solid theoretical knowledge and skills, solid technical skills and knowledge and training in how to make ethical judgments. The basic requirement for training in gastrointestinal endoscopy should be that the student is enrolled in a clinical, surgical or pediatric gastroenterology subspecialty program. Responsibility for training in endoscopy should be in the hands of university professors and at well supported teaching hospitals and medical centers. The training time for basic endoscopy should be two years while advanced endoscopy requires at least another year and should be targeted towards a specific advanced field.